Uterus didelphys and cervical cancer: A case report - Annika Krückel; Miriam Saatze; Annika S. Behrens; Matthias W. Beckmann; Patrik Pöschke; Julius Emons (Elsevier, 2024)
Background: Deficiencies in the merging process of the paramesonephric ducts as part of the embryonal development lead to anomalies of the uterus, cervix, fallopian tubes and proximal vagina (Müllerian malformations). The co-occurrence with cervical cancer is rare and there are no standardized protocols for managing urogenital anomalies in the realm of oncologic treatment for gynecological carcinomas. Case report: A symptom-free 41-year-old woman (gravida 0) presented at our clinic with an externally obtained AGC-FN (atypical glandular cells - favor neoplastic) finding in the Papanicolaou (Pap) smear test and persistent positivity for human papillomavirus (HPV) type 16. Sample biopsies from the portio vaginalis uteri confirmed a cervical intraepithelial neoplasia (CIN) III/ high grade squamous intraepithelial lesion (HSIL), invasive carcinoma could not be ruled out. The examinations revealed the incidental finding of a uterus didelphys and renal agenesis on the left side. After cervical conization, the patient was diagnosed with squamous cell carcinoma of the cervix. Guideline-compliant treatment with laparotomic hysterectomy according to Piver type II following a staging laparoscopy with sentinel lymphadenectomy was performed. A customized protocol was used for the indocyanine green (ICG) injection as part of the sentinel lymph node examination, tailored to the patient's anatomical characteristics. Discussion: Müllerian malformations may impede detection and treatment of gynecological carcinomas. Individualized therapy planning is necessary to meet the anatomical peculiarities of the genital anomaly. In instances of concomitant urinary tract anomalies, protective measures are imperative to safeguard normal kidney function. Conclusion: The current case demonstrates the successful implementation of guideline-compliant therapy for early-stage cervical cancer in an individual with Müllerian malformation.